2015
DOI: 10.1016/j.chembiol.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Opposite Effects of hRAD51 Chemical Modulation on HIV-1 Integration

Abstract: SUMMARY The cellular DNA repair hRAD51 protein has been shown to restrict HIV-1 integration both in vitro and in vivo. To investigate its regulatory functions, we performed a pharmacological analysis of the retroviral integration modulation by hRAD51. We found that, in vitro, chemical activation of hRAD51 stimulates its integration inhibitory properties, whereas inhibition of hRAD51 decreases the integration restriction, indicating that the modulation of HIV-1 integration depends on the hRAD51 recombinase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Consistent with this, resveratrol inhibits HIV-1 expression in a HeLa cell line containing an integrated HIV-1 promoter-reporter module via the activation of SIRT1 (25). The concentrations of resveratrol and pterostilbene used to achieve half-maximum inhibition of HIV-1 integration (78) and Tat transactivation (25) (47.5 M and 50 M, respectively) were up to 10 times higher than the concentration that we found completely inhibited HIV-1 in resting CD4 T cells (5 M). Indeed, Fontecave et al showed that 10 M resveratrol can completely destroy the catalytic tyrosyl radical in a biochemical assay (20), and this concentration closely matched the IC 90 of resveratrol in our model.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Consistent with this, resveratrol inhibits HIV-1 expression in a HeLa cell line containing an integrated HIV-1 promoter-reporter module via the activation of SIRT1 (25). The concentrations of resveratrol and pterostilbene used to achieve half-maximum inhibition of HIV-1 integration (78) and Tat transactivation (25) (47.5 M and 50 M, respectively) were up to 10 times higher than the concentration that we found completely inhibited HIV-1 in resting CD4 T cells (5 M). Indeed, Fontecave et al showed that 10 M resveratrol can completely destroy the catalytic tyrosyl radical in a biochemical assay (20), and this concentration closely matched the IC 90 of resveratrol in our model.…”
Section: Discussionmentioning
confidence: 53%
“…Resveratrol and, presumably, pterostilbene target cellular pathways other than the RNR pathway (3,4,(71)(72)(73)(74)(75)(76)(77). Pterostilbene can inhibit HIV-1 integrase in vitro and partially inhibit HIV-1 infection of a transformed fibroblastic cell line, 293T (19,78). Most prominent among the known resveratrol and pterostilbene targets is activation of Sirtuin 1 (SIRT1), an NAD ϩ -dependent deacetylase (79).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the base excision repair (BER) pathway was in part confirmed by biochemical and genetic studies [1517]. RAD51 protein, which is an important player in HR, was found to affect HIV-1 integration [18, 19]. The involvement of the NHEJ pathway in HIV-1 replication has undergone particularly extensive studies providing numerous data showing that depletion of proteins involved in this pathway decreases HIV-1 infectivity [9, 2025].…”
Section: Introductionmentioning
confidence: 99%
“…For the provirus to integrate, a double strand DNA break is required. HIV-1 integration is linked to RAD51 (Thierry et al, 2015), and through the viral Vpr protein, HIV-1 extensively engages several DNA damage response pathways (Li et al, 2020). Vpr plays a key role by inhibiting specific pathways of the DNA repair and also inducing cell cycle arrest and upregulating p21 (Vaźquez et al, 2005).…”
Section: Hiv-1 Interacts With Dna Damage Response Pathwaysmentioning
confidence: 99%